Civilians and soldiers : achieving better coordination - Pirnie, Bruce, 1940- (RAND, National Security Research Division, 1998)
Since 1989, the United States has embarked on numerous complex contingency operations overseas--especially in Somalia, Haiti, and Bosnia--requiring a high degree of coordination between the civilian and military sides of the operations. What has the U.S. government learned and failed to learn from its experience? The author examines the erratic performance of the U.S. in these contingencies and looks at several working models of the interagency process and ways to improve communication between civilian and military communities. After analyzing the problems of the past, the report offers recommendations to decisionmakers in the Executive Branch to improve chances of success in future complex contingency operations through more coherent U.S. policy and strategy.